America's need for an ‘Ethical Renaissance’ - Hatfield, Mark O. (Journal of business ethics, 1982)
Remember the words of Cain, “Am I my brother's keeper?” God said to him that “his brother's blood cries out from the ground”. What do these words suggest for the role of government? I assert that there is an ethic of accountability, caring and sharing fundamental to individual and corporate life. Creation was provided for all humanity. Until we can grasp a global view of resource stewardship we cannot begin to consider wise utilization. The goal must be an ethical renaissance that will bring security more effective than any military force.